Building school leaders’ instructional leadership capacity through virtual professional leadership learning communities - Pashmforoosh, Roya; Irby, Beverly J.; Lara-Alecio, Rafael; Tong, Fuhui (Frontiers in Education, 2023)
Introduction Research is still emerging on how to develop school leaders’ instructional capacity. We implemented research-based practices through virtual professional leadership learning communities (VPLCs) for building school leaders’ instructional capacity. We examined school leaders’ perceptions of (a) the effectiveness of the VPLC as a vehicle for improving instructional practices, (b) the essential components of an effective VPLC, and (c) school leaders’ instructional leadership practices through discussions within VPLC. Methods The participants of this study were 40 school leaders at the principal and assistant principal levels in elementary schools in the state of Texas. Based on the research purpose and design, multiple types of data were collected to explore participants’ perceptions and experiences of VPLC. Results Based on both qualitative and quantitative analyses of the data from questionnaires and interviews, we found that this VPLC allowed participants to share leadership research and resources and provided them with an avenue for collaborating and communicating with other school leaders. The results of the qualitative data revealed two major components that the participants thought a VPLC should provide based on their experiences in the program (a) community building through collaboration and (b) reflective modules and discussion. Discussion An SST explanation can potentially reduce some aspects of homophobia among both healthcare professionals and lay people. Also, worryingly, Chinese healthcare professionals, especially medical professionals, reported more homophobia than lay individuals These VPLCs were regarded as grounds for innovation, as participants worked together with other school leaders to find problems and determine creative and workable solutions focused on building instructional capacity in serving high-needs schools. Thus, school leaders can be supported through sustained, effective professional learning in communities of practice, or virtual professional leadership learning communities.